The Congressional Budget Office : honest numbers, power, and policymaking - Joyce, Philip G., 1956- (American governance and public policy., 2011)
Created in 1974, the U.S. Congressional Budget Office (CBO) has become one of the most influential forces in national policymaking. A critical component of our system of checks and balances, the CBO has given Congress the analytical capacity to challenge the president on budget issues while it protects the public interest, providing honest numbers about Congress's own budget proposals. The book discusses the CBO's role in larger budget policy and the more narrow "scoring" of individual legislation, such as its role in the 2009--2010 Obama health care reform. It also describes how the first ...